Cost-effectiveness analysis of radiofrequency ablation versus drugs for the treatment of a trial fibrillation in the South African population - Henry-Lines, Heather (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.